Potret Tilawah Al-Qur’an: Analisis Lahn Membaca Al-Qur’an (Studi Pada Mahasiswa IAIN Langsa, Aceh) - Mulizar Mulizar; Awaluddin Awaluddin (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2022)
This study aims to describe what and forms of errors (lahn) in reading the Qur'an. This paper is the result of a case study using a descriptive analysis method with a qualitative approach, where the main data sources are observation and interviews in the form of tests, and documentation. The results of this study explain that the error (Lahn) in reading the Qur'an to students is in the mention of the hijaiyah letters that are not in place, then the type of error (lahn) hijaiyah letters that students often make when reading the Qur'an is the letters (lha), ('ain), (ha), and (dza) and the more dominant error (lahn) is lahn khufi compared to lahn jali. Then the problems faced by students are the main categories in recitation problems, then fluency with the type of letters that are less fluent when pronouncing hijaiyah letters, namely the main letters are (lha), (dhad), (ghain), (dza), ( ha), then it is difficult to distinguish the length of the short reading and fluency in reading so that there are still stuttering in reading.